1994
DOI: 10.1161/01.cir.89.2.567
|View full text |Cite
|
Sign up to set email alerts
|

Apolipoprotein polymorphisms fail to define risk of coronary artery disease. Results of a prospective, angiographically controlled study.

Abstract: Despite the fundamental role of apolipoprotein genes in lipid metabolism, we find no evidence that common genetic polymorphisms of the major apolipoprotein loci have a significant influence on the risk of developing angiographically defined CAD in this representative population. Therefore, at this time we find no support for the hypothesis that mass screening for genetic polymorphisms at candidate loci can reduce the burden of CAD by identifying a substantial proportion of high-risk individuals. Instead, it ap… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
21
0

Year Published

1995
1995
2015
2015

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 62 publications
(23 citation statements)
references
References 39 publications
2
21
0
Order By: Relevance
“…31 Marshall et al found no evidence that the apoB Ins/Del polymorphism had a significant influence on the risk of angiographically defined CAD. 39 In contrast, Hong et al observed that the Ins allele frequency was significantly higher in patients than in healthy controls in a Korean case control study with 216 controls and 235 CAD patients. 26 In order to generate robust data on apoB gene (EcoRI, XbaI, and SpIns/Del) polymorphisms and CAD risk, we carried out an update meta-analysis involving 54 studies and focusing on worldwide studies to provide the most comprehensive analysis on the relationship between apoB gene polymorphisms and CAD risk.…”
Section: Discussionmentioning
confidence: 89%
“…31 Marshall et al found no evidence that the apoB Ins/Del polymorphism had a significant influence on the risk of angiographically defined CAD. 39 In contrast, Hong et al observed that the Ins allele frequency was significantly higher in patients than in healthy controls in a Korean case control study with 216 controls and 235 CAD patients. 26 In order to generate robust data on apoB gene (EcoRI, XbaI, and SpIns/Del) polymorphisms and CAD risk, we carried out an update meta-analysis involving 54 studies and focusing on worldwide studies to provide the most comprehensive analysis on the relationship between apoB gene polymorphisms and CAD risk.…”
Section: Discussionmentioning
confidence: 89%
“…Thus, APOB is critical for the synthesis, transport, and catabolism of TG-rich and cholesterol-rich lipoproteins in the intestine and liver ( 11,12 ). Polymorphisms in the APOB gene have been associated with the variability of serum cholesterol levels and coronary atherosclerosis in some populations ( 13 ) but not all ( 14 ). No studies have examined the role of APOB genetic variants in relation to the lipid-lowering effects of fenofi brate.…”
Section: Discussionmentioning
confidence: 99%
“…The e4 allele has been implicated in some studies as a risk factor for CAD (11,42,(45)(46)(47), although others have failed to find such an association, including a prospective angiographic study (37,(48)(49)(50). In the Scandinavian Simvastatin Survival Study, Gerdes et al (12) concluded that patients carrying the e4 allele have an 80% increased risk of coronary death compared with patients not carrying the allele.…”
Section: Discussionmentioning
confidence: 99%